1998
DOI: 10.1029/98gl00756
|View full text |Cite
|
Sign up to set email alerts
|

Observed coupling of the mesosphere inversion layer to the thermal tidal structure

Abstract: Abstract. Rayleigh lidar observations of mesosphere temperature profiles obtained from 40 to -100 km from Logan, Utah (41.7, 111.8 W, altitude, 1.9 km) over 10 nights in late February, 1995, revealed an interesting development between 60 to 75 km of a winter mesosphere inversion layer with an amplitude of -20-30 K and a downward phase progression of -1 km/hr. The data also showed two altitude regions exhibiting significant cooling of 10-30 K in extent. These were located below and above the peak of the inversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 21 publications
2
68
1
Order By: Relevance
“…The heating rates obtained by Lübken are ∼ 13 K/d around 90 km in summer and 1-2 K/d at 80-100 km in winter. Recently, Meriwether et al (1998) suggested that the mesospheric inversions observed by the Rayleigh lidar during February 1995 at Logan, Utah are caused by a localized mechanism involving the coupling of gravity waves to the mesopause tidal structure. Liu and Hagen (1998) have demonstrated through a simulation the effect of gravity wave-tidal interaction on the mesosphere -lower thermosphere thermal structure.…”
Section: Observations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heating rates obtained by Lübken are ∼ 13 K/d around 90 km in summer and 1-2 K/d at 80-100 km in winter. Recently, Meriwether et al (1998) suggested that the mesospheric inversions observed by the Rayleigh lidar during February 1995 at Logan, Utah are caused by a localized mechanism involving the coupling of gravity waves to the mesopause tidal structure. Liu and Hagen (1998) have demonstrated through a simulation the effect of gravity wave-tidal interaction on the mesosphere -lower thermosphere thermal structure.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…From in situ rocket measurements at high latitudes, however, Lübken (1997) showed that the turbulent heating rates are fairly small (∼1-2 K/d) for winter, although significantly high (∼10-20 K/d) around the summer mesopause (∼90 km). The role of semi-diurnal and diurnal tides in causing the inversions has been studied by Meriwether et al (1998) by comparing the observed mesosphere thermal structure with that predicted by a Global Scale Wave Model (GSWM) for a mid-latitude. In finding the observed amplitudes of heating and cooling to be about 10 times larger than the predicted GSWM values, they suggested that the inversions are possibly caused through an amplification mechanism based upon the interactions of the gravity waves with the tidal structure (Liu and Hagen, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, the temperature enhancements are much larger than the Global Scale Wave Model (GSWM) diurnal tidal predictions, which leads to the conjecture that gravity wave-tidal interaction might play an important role in the layer formation [Meriwether et al, 1998]. In this work, a two dimensional nonlinear numerical model is employed to study the propagation of a gravity wave in a diurnal tidal wind field and its local thermal and dynamical impacts on the tidal structure.…”
mentioning
confidence: 99%
“…Both the NCAR general circulation model and the Global Scale Wave Model predicted similar and smaller amplitudes than the observed. Meriwether et al (1998) suggested that the enhancement of the MIL amplitude to temperatures considerably elevated above that represented by the tidal structure alone may be indicative of dynamical forcing. A possible source for this was suggested to be gravity waves interacting with tidal wave activity.…”
Section: Introductionmentioning
confidence: 99%